Cycles inside cycles: Spanish regional aggregation - Maria Dolores Gadea; Ana Gómez-Loscos; Antonio Monta\~nés (SERIEs - Journal of the Spanish Economic Association, 2012)
This paper sets out a comprehensive framework to identify regional business cycles within Spain and analyses their stylised features and the degree of synchronisation both within them and between them and the Spanish economy. We show that the regional cycles are quite heterogeneous although they display some degree of synchronisation. We also propose a dynamic factor model to cluster the regional comovements. We find that the Spanish business cycle is not the same as those of the 17 regions, but is the sum of the different regional behaviours. Clusters with a high industrial weight, per capita income and human capital and a low unemployment rate are also more synchronized. The implications derived from our results are useful both for policy makers and analysts.
Keywords: C22; C32; E32; R11; 330; business cycle; synchronisation measures; dynamic factor models; regional policy; Regionaler Konjunkturzyklus; Konjunkturzusammenhang; Regionalpolitik; Spanien